2021
DOI: 10.1016/j.isci.2021.103241
|View full text |Cite
|
Sign up to set email alerts
|

The ubiquitin ligase HOIL-1L regulates immune responses by interacting with linear ubiquitin chains

Abstract: Summary The Linear Ubiquitin Chain Assembly Complex (LUBAC), composed of HOIP, HOIL-1L, and SHARPIN, promotes tumor necrosis factor (TNF)-dependent NF-κB signaling in diverse cell types. HOIL-1L contains an Npl4 Zinc Finger (NZF) domain that specifically recognizes linear ubiquitin chains, but its physiological role in vivo has remained unclear. Here, we demonstrate that the HOIL-1L NZF domain has important regulatory functions in inflammation and immune responses in mice. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 55 publications
2
6
0
Order By: Relevance
“…In agreement with the data published using ubiquitin dimers (Sato et al , 2011 ; Gomez‐Diaz et al , 2021 ), we found that the mutation or loss of the NZF domain was sufficient to disrupt the binding of HOIL‐1 to immobilised Halo‐tagged M1‐Ub tetramers (Fig EV4C and D ). This indicates that constructs containing the RBR domain, but lacking the NZF domain of HOIL‐1, have a much lower affinity for the M1‐Ub tetramer than constructs containing the NZF domain.…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…In agreement with the data published using ubiquitin dimers (Sato et al , 2011 ; Gomez‐Diaz et al , 2021 ), we found that the mutation or loss of the NZF domain was sufficient to disrupt the binding of HOIL‐1 to immobilised Halo‐tagged M1‐Ub tetramers (Fig EV4C and D ). This indicates that constructs containing the RBR domain, but lacking the NZF domain of HOIL‐1, have a much lower affinity for the M1‐Ub tetramer than constructs containing the NZF domain.…”
Section: Resultssupporting
confidence: 92%
“… HOIL‐1[T203A/F204A/R210A] was assayed at 30°C in the absence or presence of the indicated ubiquitin dimers and tetramers. These mutations have been reported to impair the binding of ubiquitin to the NZF domain (Sato et al , 2011 ; Gomez‐Diaz et al , 2021 ) and their approximate location in HOIL‐1 is indicated (schematic not to scale). Assay of HOIL‐1[Δ194‐222] lacking the NZF core domain at 30°C in the absence or presence of the indicated ubiquitin oligomers.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations